Seasonality and temperature-dependent flight dispersal of Triatoma infestans (Hemiptera: Reduviidae) and other vectors of Chagas disease in Western Argentina - Di Iorio, Osvaldo Rubén (2017)
Flight dispersal of Triatominae is affected by climatic conditions and determines the spatiotemporal patterns of house invasion and transmission of Trypanosoma cruzi Chagas (Kinetoplastida: Trypanosomatidae). We investigated the detailed time structure and temperature dependencies of flight occurrence of Triatoma infestans Klug (Hemiptera: Reduviidae) and other triatomine species in a rural village of western Argentina by taking advantage of the attraction of adult triatomines to artificial light sources. Most of the village's streetlight posts were systematically inspected for triatomines twice between sunset and midnight over 425 nights in the spring-summer seasons of 1999-2002, an unprecedented light-trap sampling effort for any triatomine species. In total, 288 adults were captured, including 122 Triatoma guasayana Wygodzinsky and Abalos, 89 T. infestans, 72 Triatoma eratyrusiformis Del Ponte, and 5 Triatoma garciabesi Carcavallo et al. Adult sex ratios were balanced in T. infestans and strongly male-biased in other species. Nearly all flight-dispersing triatomines were caught when temperatures at sunset were >20 °C (range, 16.6-31.7 deg;C), suggesting a putative threshold around 17-18 deg;C. Triatomine catches were rare on rainy days. Logistic regression analysis revealed that the proportion of nights in which at least an adult T. infestans was caught increased highly significantly with increasing temperature at sunset and was modified by collection month, with greater catches in early spring and no sex differential. This study confirms that spring represents a previously overlooked, important dispersal period of T. infestans, and shows large variations among and within Triatominae in their temporal patterns of flight occurrence, abundance, and sex ratio.